2014
DOI: 10.15698/mic2014.07.154
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous addition of histidine reduces copper availability in the yeast Saccharomyces cerevisiae

Abstract: The basic amino acid histidine inhibited yeast cell growth more severely than lysine and arginine. Overexpression of CTR1, which encodes a high-affinity copper transporter on the plasma membrane, or addition of copper to the medium alleviated this cytotoxicity. However, the intracellular level of copper ions was not decreased in the presence of excess histidine. These results indicate that histidine cytotoxicity is associated with low copper availability inside cells, not with impaired copper uptake. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Although they are essential metabolites, it has been known for over half a century that the addition of excess amino acids to both prokaryotic and eukaryotic cell cultures can cause growth inhibition and/or cell death (Rowley 1953a(Rowley , 1953bJohnson and Vishniac 1970;Jensen et al 1974;Englesberg et al 1976;Sumrada and Cooper 1976;Nishiuch et al 1976;Miles et al 1976). The dependence of toxicity on transport activity indicate that the effect is exerted intracellularly (Kaur and Bachhawat 2007;Watanabe et al 2014). In humans, several inherited metabolic diseases are caused by elevated levels of amino acids and/or closely related metabolites, with perhaps the most well known being phenylketonuria (Blau et al 2010;Saudubray et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they are essential metabolites, it has been known for over half a century that the addition of excess amino acids to both prokaryotic and eukaryotic cell cultures can cause growth inhibition and/or cell death (Rowley 1953a(Rowley , 1953bJohnson and Vishniac 1970;Jensen et al 1974;Englesberg et al 1976;Sumrada and Cooper 1976;Nishiuch et al 1976;Miles et al 1976). The dependence of toxicity on transport activity indicate that the effect is exerted intracellularly (Kaur and Bachhawat 2007;Watanabe et al 2014). In humans, several inherited metabolic diseases are caused by elevated levels of amino acids and/or closely related metabolites, with perhaps the most well known being phenylketonuria (Blau et al 2010;Saudubray et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Valine and phenylalanine inhibit the growth of bacterial cells by repressing enzymes involved in synthesis of isoleucine and tyrosine, respectively (Leavitt and Umbarger 1962;Bhatnagar et al 1989). Histidine toxicity in yeast cells is caused by a reduction in copper availability in vivo (Watanabe et al 2014). There is also evidence for a more general mechanism involving the target of rapamycin complex 1 (TORC1), a master controller of cell metabolism that is conserved among eukaryotes and responds to various nutrient stimuli including amino acids (Duan et al 2015;Powis and De Virgilio 2016;Zheng et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the addition of amino acids promoted the excretion of ERG in the stationary phase. We hypothesized that this was due to cell death because of the toxic effects of the added amino acids, in particular histidine (Watanabe et al, 2014) and cysteine (Kumar et al, 2006). Indeed propidium iodide staining of cells sampled every 24 hours for 72 hours, showed an increase in the fraction of dead cells from 9 to 70%, when amino acids were added at concentrations of 1 g/L (supplementary figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…As an example to validate the observations reached in the above non-biased study, we examined the sensitivity of S. pombe to exogenous histidine, which is not an essential amino acid for this organism. While a lower amount of exogenous histidine usually promotes the growth of yeasts, at high concentrations it is known to generate cytotoxicity and requires the actions of the histidine/amidazole synthesis/metabolism pathway for mitigation (Winkler and Ramos-Montanez, 2009;Watanabe et al, 2014;Duncan et al, 2018). When we compared the growth rates of the yeasts hosting the ate1-deletion to the control cells, we found that, although there is no apparent difference in their proliferation in the absence of exogenous histidine 1 www.pantherdb.org (Figure 3A), ate1-deleted yeast grow much slower than the control in high concentrations of histidine (Figures 3B-E).…”
Section: Genes That Genetically Interact With Ate1 Can Be Clustered Bmentioning
confidence: 99%